A case study in electrical & electronic industry using mahalanobis-taguchi system and time-driven activity-based costing on production environment - Nik Nurharyantie, Nik Mohd Kamil (2021)
Electrical and electronic industry is one of Malaysia’s leading industries which covers around 24.5% in manufacturing production sector. With continuous innovation in electrical and electronic industry, the demands for magnetic component are increasing. To produce good finishing products and optimize the company production operations, significant parameters that contribute towards these areas are very important. Thus, by solely relying on the control chart to confirm the significant parameter is not sufficient. Meanwhile, the activity-based costing being applied is quite obsolete because the method ignores the potential of time equation and capacity cost rate with significant parameters to measure the un-used capacity. Therefore, in order to prove that the proposed methods are practicable, it should be applied at different complexity of product. The main objective of this research is to validate the method of MahalanobisTaguchi system (MTS) and time-driven activity-based costing (TDABC) at inductor component workstation. The collection data is obtained from a company located in Kuantan, Pahang which focuses on the magnetic component production. MTS optimizes 10 parameters at magnetic component workstation and 7 parameters at inductor component workstation. Meanwhile, TDABC determines the un-used capacity by considering the significant parameters after developing the time equation and capacity cost rate. During the analysis of magnetic component, height of excess plastic header is consistently unaffected the operation. The parameter is classified as significant and it should be removed to eliminate any waste. Number of scratches and number of epoxy spot on winding coil are inconsistently affected the operation. These parameters are classified as insignificant and they should be maintained at this moment. Through the implementation of TDABC on the un-used capacity of time, the most overutilized sub-activities belongs to put the epoxy at the 4 leadout within core and header in epoxy application with -41,572,800 minutes and the smallest utilized portion belongs to insert the unit into the holder in epoxy application with 475,199.56 minutes. For the un-used capacity of cost, the most over-utilized sub-activities belongs to put the epoxy at the 4 leadout within core and header in epoxy application with MYR-189,571,968.00 and the smallest utilized portion belongs to transfer wound core to the forming machine in forming and pre-cutting with MYR4,273,234.92. During the analysis of inductor component for validation, condition of core is consistently unaffected the operation. The parameter is classified as significant and it should be removed to eliminate any waste. Condition of wire and condition of epoxy are inconsistently affected the operation. These parameters are classified as insignificant and they should be maintained at this moment. For the un-used capacity of time, the largest utilized portion belongs to take out the unit part from PVC tube and put on magnetic fixture in tape & reel with 8,397 minutes and for the un-used capacity of cost, the largest utilized portion belongs to the same sub-activity with MYR419.85. Therefore, this research successfully proves that the method of MTS and TDABC are practicable in mass production with different complexity of product.